The Effectiveness of The Restructuring Mechanism of Bank Muamalat on Murabahah Financing Products during Pandemic Covid 19 - Fauziah, Nur Dinah; Satria, Yudha; Andayani, Hirini (ekonomi syariah, 2023)
The Covid-19 pandemic has caused many industries desperate due to the limitations of existing activities, including the financial services industry. Since the Covid-19 pandemic arrived in Indonesia, at least this has largely affected Indonesia's national economy. Covid-19 pandemic has certainly not only disrupted economic activity in Indonesia but in almost all countries in the world. Limited activity during this pandemic has paralyzed economic activity globally and nationally. Banks as the forefront that have the power to stabilize and maintaining financial stability must work hard to overcome the impacts that have occurred due to Covid-19 pandemic. The Restructuring mechanism is one of the products launched to overcome Non Performing Credit from customers due to the impact of the Covid-19 pandemic. This study is an analysis study using secondary data. This study describes the effectiveness of the implementation of Restructuring during the Covid-19 pandemic. The results of this study will be useful as a reference for making future policies regarding regulatory in handling such phenomena that may occur as a pre-cautious mechanism.